Direct UV-induced functionalization of surface hydroxy groups by thiol-ol chemistry - Li, Linxian; Li, Junsheng; Du, Xin; Welle, Alexander; Grunze, Michael; Trapp, Oliver; Levkin, Pavel (Angewandte Chemie. International edition, 2014)
A novel UV-initiated surface modification method for the direct functionalization of surface hydroxy groups with thiol-containing molecules (termed “thiol-ol” modification) is described. This method is based on the oxidative conjugation of thiols to hydroxy groups. We demonstrate that different thiol-containing molecules, such as fluorophores, thiol-terminated poly(ethylene glycol) (PEG-SH), and a cysteine-containing peptide, can be attached onto the surface of porous poly(2-hydroxyethyl methacrylate-co-ethylene dimethacrylate). Direct functionalization of other hydroxy-group-bearing surfaces, fabrication of micropatterns, and double patterning have been also demonstrated using the thiol-ol method.